THE USE OF SPRINKLER IRRIGATION IN CULTIVATION OF VARIOUS CROPS - Djumanazarova Altingul Tengelovna; Imiyanova Risolathon Numanovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article presents the optimal conditions for the development of crops, created during irrigation by pulsed sprinkling, which contributes to an increase in productivity up to 15-20%, which will solve the issues of ensuring the country’s food security.